Multimedia and children in Turkey - Tuncer, A. Murat; Yalçın, S. Songül (The Turkish Journal of Pediatrics, 1999)
Multimedia will be regarded as essential tools for children to create their new world. The effects of television on young children’s life have been well studied. Television differs, however, from other media, including the movies, in its pervasive impact on children. Children spend more time watching television than any other activity except sleeping. Overall 31% of children spent at least 4 hours a day watching television during weekday and 71.7% during weekend in Turkey. Television’s influence on children is a function of the length of time they spend watching and the cumulative effect of what they see. Television may be a cause as well as a solution for many serious childhood problems. Excessive viewing of television has also been linked to aggressive behavior, violence, childhood obesity. On the other hand, television may act as a socializing agent and as a learning tool if the recommendations of American Academy of Pediatrics is learned by pediatricians, parents and broadcasters. The use of home personal computers in urban residence increased from 3.2% in 1993 to 6.5% by January 1998 in Turkey. Around 20% of computer households reported owing a modem. Internet has been using only for 5 years in Turkey. Nearly 40% of computer households also used CD-ROM equipment. The percentage of schools that have a computer laboratory is only 2.64%. On the other hand, multimedia allows students to move away from a uniform education for everyone to assert individual identity, liberalize education and management. It seems likely that, within the next few years, most of the countries with substantial internet infrastructure will use the internet as the major medium for disseminating information, including information on children. To prepare students for such a world demands that educational systems make the best possible use of all knowledge and technologies currently available.